UTILIZATION OF PRAWN WASTE-ISOLATION OF CHITIN AND ITS CONVERSION TO CHITOSAN - MADHAVAN, P; RAMACHANDRAN NAIR, K G (Fishery Technology, 2017)
A process is described for the preparation of chitosan from prawn waste. The process involves extraction of protein using 0.5% sodium hydroxide solution, bleaching the protein free mass with bleach liquor containing 0.3-0.5% available chlorine followed by demineralisation with 1.25 N hydrochloric acid in the cold and deacetyiation using 1:1 (w jw) sodium hydroxide solution at 100Â°C for 2 hours.